From Parent to Gamete: Vertical Transmission of Symbiodinium (Dinophyceae) ITS2 Sequence Assemblages in the Reef Building Coral Montipora capitata - Padilla-Gamiño, Jacqueline L.; Pochon, Xavier; Bird, Christopher; Concepcion, Gregory T.; Gates, Ruth D. (PLOS ONE, 2012)
Parental effects are ubiquitous in nature and in many organisms play a particularly critical role in the transfer of symbionts across generations; however, their influence and relative importance in the marine environment has rarely been considered. Coral reefs are biologically diverse and productive marine ecosystems, whose success is framed by symbiosis between reef-building corals and unicellular dinoflagellates in the genus Symbiodinium. Many corals produce aposymbiotic larvae that are infected by Symbiodinium from the environment (horizontal transmission), which allows for the acquisition of new endosymbionts (different from their parents) each generation. In the remaining species, Symbiodinium are transmitted directly from parent to offspring via eggs (vertical transmission), a mechanism that perpetuates the relationship between some or all of the Symbiodinium diversity found in the parent through multiple generations. Here we examine vertical transmission in the Hawaiian coral Montipora capitata by comparing the Symbiodinium ITS2 sequence assemblages in parent colonies and the eggs they produce. Parental effects on sequence assemblages in eggs are explored in the context of the coral genotype, colony morphology, and the environment of parent colonies. Our results indicate that ITS2 sequence assemblages in eggs are generally similar to their parents, and patterns in parental assemblages are different, and reflect environmental conditions, but not colony morphology or coral genotype. We conclude that eggs released by parent colonies during mass spawning events are seeded with different ITS2 sequence assemblages, which encompass phylogenetic variability that may have profound implications for the development, settlement and survival of coral offspring.